Green finance innovation and carbon neutrality strategies: sustainable development pathways and policy frameworks - Dong, Xueqin; Dong, Dongdong; Yu, Qing (Frontiers in Environmental Science, 2024)
IntroductionThis paper analyzes the influence of green finance innovation on the green innovation ability of Shanxi Huangtupo Coal Industry Group Co., Ltd.MethodsBy constructing a fixed-effect model. This study uses the number of green patent applications by enterprises as indicator to measure green innovation, with the green finance development index as a key explanatory variable, while controlling for other factors such as asset-liability ratio and listing time.ResultsThe results show that there is a significant positive correlation between green finance innovation and the green innovation of enterprises, indicating that the development of green finance has effectively promoted the green technology innovation in enterprises, which helps to achieve carbon neutrality.DiscussionThe study provides a reference for policymakers to promote the development of lowcarbon economy through financial policies. Linking green finance innovation with the green innovation capabilities of specific high emission sector enterprises provides new insights into the role of green finance in promoting enterprise carbon neutrality.